Nutrients and bioactives in green leafy vegetables and cognitive decline: Prospective study. (16th January 2018) - Morris, Martha Clare; Wang, Yamin; Barnes, Lisa L.; Bennett, David A.; Dawson-Hughes, Bess; Booth, Sarah L.
Abstract : Objective: To increase understanding of the biological mechanisms underlying the association, we investigated the individual relations to cognitive decline of the primary nutrients and bioactives in green leafy vegetables, including vitamin K (phylloquinone), lutein, β-carotene, nitrate, folate, kaempferol, and α-tocopherol. Methods: This was a prospective study of 960 participants of the Memory and Aging Project, ages 58–99 years, who completed a food frequency questionnaire and had ≥2 cognitive assessments over a mean 4.7 years. Results: In a linear mixed model adjusted for age, sex, education, participation in cognitive activities, physical activities, smoking, and seafood and alcohol consumption, consumption of green leafy vegetables was associated with slower cognitive decline; the decline rate for those in the highest quintile of intake (median 1.3 servings/d) was slower by β = 0.05 standardized units ( p = 0.0001) or the equivalent of being 11 years younger in age. Higher intakes of each of the nutrients and bioactives except β-carotene were individually associated with slower cognitive decline. In the adjusted models, the rates for the highest vs the lowest quintiles of intake were β = 0.02, p = 0.002 for phylloquinone; β = 0.04, p = 0.002 for lutein; β = 0.05, p < 0.001 for folate; β = 0.03, p = 0.02 for α-tocopherol; β = 0.04, p = 0.002 for nitrate; β = 0.04, p = 0.003 for kaempferol; and β = 0.02, p = 0.08 for β-carotene. Conclusions: Consumption of approximately 1 serving per day of green leafy vegetables and foods rich in phylloquinone, lutein, nitrate, folate, α-tocopherol, and kaempferol may help to slow cognitive decline with aging.